Financial toxicity and its associations with health-related quality of life among urologic cancer patients in an upper middle-income country - Ting, Chuo Yew; Teh, Guan Chou; Yu, Kong Leong; Alias, Haridah; Tan, Hui Meng; Wong, Li Ping (Springer Verlag (Germany), 2020)
Purpose: This study examined the prevalence of financial toxicity (FT) and associated factors among urologic cancer patients. The association between FT and health-related quality of life (HRQoL) was also investigated. Methods: A total of 429 respondents diagnosed with urologic cancers (prostate cancer, bladder and renal cancer) from Sarawak General Hospital and Subang Jaya Medical Centre in Malaysia were interviewed using a structured questionnaire. Objective and subjective FT were measured by catastrophic health expenditure (healthcare-cost-to-income ratio greater than 40%) and the Personal Financial Well-being Scale, respectively. HRQoL was measured with the Functional Assessment of Cancer Therapy – General 7 Items scale. Results: Objective and subjective FT were experienced by 16.1 and 47.3% of the respondents, respectively. Respondents who sought treatment at a private hospital and had out-of-pocket health expenditures were more likely to experience objective FT, after adjustment for covariates. Respondents who were female and had a monthly household income less than MYR 5000 were more likely to experience average to high subjective FT. Greater objective FT (OR = 2.75, 95% CI 1.09–6.95) and subjective FT (OR = 4.68, 95% CI 2.63–8.30) were associated with poor HRQoL. Conclusions: The significant association between both objective and subjective FT and HRQoL highlights the importance of reducing FT among urologic cancer patients. Subjective FT was found to have a greater negative impact on HRQoL. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.